Effects of a combination of herbal extracts (modified Ojayeonjonghwan (Wuzi Yanzong wan)) on partial urethral obstruction-induced detrusor overactivity in rats: impact on the nitric oxide pathway and oxidative stress - Sangrak Bae; Kyu Won Lee; Hyun Cheol Jeong; Bong Hee Park; Woong Jin Bae; Chang Hee Han; Sae Woong Kim (BMC, 2019)
Abstracts Background We investigated the effects of a berry mixture formula (modified Ojayeonjonghwan (Wuzi Yanzong Wan, MO formula) on detrusor overactivity (DO). Methods The MO formula consisted of 5 seeds obtained from 5 types of berry plants. Twenty-four Sprague-Dawley rats were randomly assigned to four groups: sham-operated (control), partial urethral obstruction-induced DO (DO group), 0.03 mg/kg solifenacin-treated DO (solifenacin group) and 200 mg/kg MO formula -treated DO (berry mixture). The control and overactive groups were administered distilled water for 4 weeks, and the solifenacin and MO formula groups were treated with the respective medication for 4 weeks. After treatment, cystometrography was performed. At the endo of cystometrography, their bladder tissues were used for identifying the muscarinic receptors, endothelial nitric oxide synthase(eNOS), RhoA, Rock-I & II, 8-hydroxy-2' -deoxyguanosine(8-OHdG), superoxide dismutase(SOD), interleukin-6 &-8(IL-6, IL-8), and tumor necrosis factor-alpha(TNF-a). The tissues were stained and the muscle-to-collagen ratio was identified. Results The presence of the muscarinic receptors were not significantly different between the solifenacin and MO formula groups. However, significant differences were found between the solifenacin and MO formula groups in terms of eNOS, RhoA, Rock-I and -II levels. The muscle-to-collagen ratio was statistically lower in the DO and solifenacin groups; however, no significant difference was observed between the control and MO formula groups. Under oxidative stress, SOD showed a similar result as 8-OHgG. The MO formula group exhibited anti-inflammatory effects, showing that no significant difference was found between the control and MO formula groups regarding values of IL-6, IL-8, and TNF-a. However, the DO and solifenacin groups showed increased IL-6, IL-8, and TNF-a levels. Cystometrography showed that the OAB and solifenacin groups having a significantly lower value than the control and MO formula groups. The mean contraction interval was shorter in the DO, MO formula, and solifenacin groups and the highest in the control group. Conclusions The MO formula exhibited a similar pharmacologic effect to that of solifenacin, with anti-inflammatory and antioxidant effects. Enhancement of the MO formula by the nitric oxide pathway affected DO including BPH-related DO. The MO formula may be one of the alternative choices of anticholinergics, a treatment for DO.